2014
DOI: 10.1155/2014/248419
|View full text |Cite
|
Sign up to set email alerts
|

Promoter Region Hypermethylation and mRNA Expression ofMGMTandp16Genes in Tissue and Blood Samples of Human Premalignant Oral Lesions and Oral Squamous Cell Carcinoma

Abstract: Promoter methylation and relative gene expression of O6-methyguanine-DNA-methyltransferase (MGMT) and p16 genes were examined in tissue and blood samples of patients with premalignant oral lesions (PMOLs) and oral squamous cell carcinoma (OSCC). Methylation-specific PCR and reverse transcriptase PCR were performed in 146 tissue and blood samples from controls and patients with PMOLs and OSCC. In PMOL group, significant promoter methylation of MGMT and p16 genes was observed in 59% (P = 0.0010) and 57% (P = 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 64 publications
1
18
0
Order By: Relevance
“…Although the current evidence is inconclusive, we observed some level of consistency in terms of loci [30] , [31] , [32] , [33] , [34] , [35] , [43] , [46] , [47] , [48] , [49] and evidence for dynamic changes during disease progression [30] , [31] . A few studies also reported concomitant dysregulated protein/mRNA expression in aberrantly methylated dysplastic oral pre-cancer [32] , [39] , [47] , [48] , [50] . Studies which analyzed methylation patterns secondary to genetic alterations such as deletions [48] , [50] indicated that aberrant methylation could be the earliest molecular change signalling disease development and progression.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Although the current evidence is inconclusive, we observed some level of consistency in terms of loci [30] , [31] , [32] , [33] , [34] , [35] , [43] , [46] , [47] , [48] , [49] and evidence for dynamic changes during disease progression [30] , [31] . A few studies also reported concomitant dysregulated protein/mRNA expression in aberrantly methylated dysplastic oral pre-cancer [32] , [39] , [47] , [48] , [50] . Studies which analyzed methylation patterns secondary to genetic alterations such as deletions [48] , [50] indicated that aberrant methylation could be the earliest molecular change signalling disease development and progression.…”
Section: Discussionmentioning
confidence: 75%
“…Longitudinal studies have reported higher hyper-methylation (p16) for dysplastic lesions that transformed to malignancy compared to lesions that regressed [30] , [31] , indicating possible dynamic alterations of methylation patterns through disease progression. p16 hyper-methylation was more frequently observed during dysplastic stages of pre-cancer than in non-dysplastic stages (hyperkeratotic/hyperplastic or non-dysplastic oral pre-cancer) [32] , [33] . Interestingly, hyper-methylation of p16 has also been found to be a promising prognostic bio-marker for recurrence-free survival of oral and oro-pharyngeal cancers [19] .…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, 42.6% of patients showed hyper-methylation of this gene both in the tumour and matched surgical margin. According to our collected literature, the frequencies of hypermethylation in HNSCC tumours vary from 86.8% 31 to 82% 32 , 49% 24 , 36% 12 , and 27% 28 to 20% 19 . Other analyses showed a significant increase in promoter hypermethylation in tumours compared to normal control tissue from the resection margin in oral cancer 33 - 35 .…”
Section: Discussionmentioning
confidence: 99%
“…A coherent methylation pattern was found in primary tumours and matched metastatic lymph nodes, and also in 65% of patient's plasma 24 . Interestingly, some studies showed methylation in patients with premalignant oral lesions and healthy controls 24 , 29 , 32 . p16 hypermethylation showed no association with clinical and demographic features in our study population, as confirmed in other studies 12 , 19 , 24 , 30 , 36 - 38 .…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that abnormal CpG islands methylation can efficiently repress the transcription of specific genes and act as one of the “hits” in the two-hit Knudson hypothesis of tumor generation [ 29 31 ]. Several authors have pointed to a relationship between DNA methylation of tumor suppressor genes such as p16 , DAPK and MGMT and the development and progression of head and neck cancers, including oral cancer [ 32 39 ]. We therefore reasoned whether aberrant methylation in promoter sites could be the cause of the downregulation observed in the genes selected from the HNSCC ORESTES libraries and started checking for this relationship using in vitro and in silico models.…”
Section: Discussionmentioning
confidence: 99%